Continuity, change and rupture in Brazilian sport: reflections from the profile of the Ministers of Sport and the budget of the Ministry of Sport - Graeff, Billy; Fernandes, Daiana Viacelli (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This chapter discusses the continuities, changes and ruptures in Brazilian sport from the profiles of the Ministers of Sport and the budget of the Ministry of Sport from 2003 to 2018. For that, we identify the sport in a social panorama that includes President Luiz Inácio Lula da Silva?s election, the choice of Brazil to host the 2014 World Cup and the Olympics 2016, the 2013 June Journeys and the 2016 coup. Data are presented on the profile of the Ministers and the resources of the Ministry of Sports in the period between 2003 and 2018 to assist a reflection on the different political and social moments the country went through in the period. The conclusions after the analysis indicated that such changes affected sport in Brazil and that more research is needed to clarify the extent of such modifications and its consequences.
Keywords: sociology of sports; sport mega events; Brazilian sport; global capitalism